2012
DOI: 10.1371/journal.pone.0043553
|View full text |Cite
|
Sign up to set email alerts
|

Hoxa11 and Hoxd11 Regulate Chondrocyte Differentiation Upstream of Runx2 and Shox2 in Mice

Abstract: During limb development, posterior Hox genes of the Hoxa- and Hoxd cluster provide positional information along the limb axis. Here we report a new function for Hoxa11 and Hoxd11 in regulating the early steps of chondrocyte differentiation. We analyzed forelimbs of Hoxa11−/−;d11−/− and Ulnaless mice, which are characterized by specifically shortened zeugopods. By detailed morphological and molecular analyses, we show that loss of Hoxa11 and Hoxd11 in the ulna of both mutants leads to an arrest of chondrocyte d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 50 publications
(66 reference statements)
1
41
0
1
Order By: Relevance
“…This sustained Hox expression in Shh −/− (Fig. 4I) could explain the favored elongation of skeletal elements, consistent with previous reports proposing that the elongation of skeletal elements requires the function of HoxA;D genes Gross et al, 2012;Zákány et al, 1997). In Shh −/− ;Gli3 −/− limb, proper elongation of skeletal elements is thus expected to be associated with HoxA;D function.…”
Section: Research Article Development 140 (10)supporting
confidence: 91%
See 1 more Smart Citation
“…This sustained Hox expression in Shh −/− (Fig. 4I) could explain the favored elongation of skeletal elements, consistent with previous reports proposing that the elongation of skeletal elements requires the function of HoxA;D genes Gross et al, 2012;Zákány et al, 1997). In Shh −/− ;Gli3 −/− limb, proper elongation of skeletal elements is thus expected to be associated with HoxA;D function.…”
Section: Research Article Development 140 (10)supporting
confidence: 91%
“…Notably, we found that during the AER phase, reducing the HoxA;D gene dose in absence of Gli3 interferes with limb bud growth in a dose-dependent manner, both along the AP and PD axes. Previous studies suggesting that the elongation of skeletal elements requires HoxA;D function were based on ubiquitous gene inactivation Gross et al, 2012;Zákány et al, 1997). Our data suggest that at least part of the reported phenotype could have been due to defective growth during the AER phase.…”
Section: ;Gli3mentioning
confidence: 99%
“…This downregulation of Shox2 expression is transient, however, as HoxA c/c ; HoxD 2/2 animals show similar Shox2 expression at E11 to wild type, despite having a drastic difference in limb bud morphology ( Figure 5). A recent report demonstrated that Hox11 genes are required for Shox2 expression in the proliferating chondrocytes of the zeugopodal elements (Gross et al 2012), suggesting Hox genes could generally function upstream of Shox2 expression in these cells. To assess whether Hox genes are necessary for Shox2 activation in the developing humerus, ISH was performed on sections of wild-type and HoxA/D mutant limbs at E14.5.…”
Section: Resultsmentioning
confidence: 99%
“…Emerging evidence indicates that the activation of Runx2 is a critical point of regulation by these genes (Cobb et al 2006;VillavicencioLorini et al 2010;Gross et al 2012). The present work supports this general model and extends it by revealing that Shox2 and Hox genes genetically interact during the development of both the stylopod and zeugopod elements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation